2007
DOI: 10.1007/s10384-007-0471-0
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Rho/Rho Kinase Signaling Pathway in Platelet-Derived Growth Factor BB-induced Vascular Endothelial Growth Factor Expression in Diabetic Rat Retina

Abstract: The Rho/Rho kinase pathway may be involved in the upregulation of VEGF expression in the diabetic retina, suggesting that fasudil might be useful for the prevention of diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 33 publications
(31 reference statements)
0
24
0
Order By: Relevance
“…This study provided new insight on the role of Rho-kinase, demonstrating that Rho-kinase may regulate intracellular translocation of transcriptional factors, likely through re-organization of actin stress fibers. Finally, we have shown that Rhokinase blockade attenuates other microvascular complications such as diabetic retinopathy [56] and neuropathy [57], as well as atherosclerosis [58]. Importantly, the effect of Rho-kinase inhibitors on diabetic complications is independent of glucose and blood pressure [51,53].…”
Section: Vldl Ldl Idlmentioning
confidence: 92%
“…This study provided new insight on the role of Rho-kinase, demonstrating that Rho-kinase may regulate intracellular translocation of transcriptional factors, likely through re-organization of actin stress fibers. Finally, we have shown that Rhokinase blockade attenuates other microvascular complications such as diabetic retinopathy [56] and neuropathy [57], as well as atherosclerosis [58]. Importantly, the effect of Rho-kinase inhibitors on diabetic complications is independent of glucose and blood pressure [51,53].…”
Section: Vldl Ldl Idlmentioning
confidence: 92%
“…In this study, ROCK inhibition by ripasudil caused intraretinal vessel growth with reduced neovascular tufts. Because it has been reported that ROCK inhibitor treatment reduced VEGF expression in diabetic retina, 32 ripasidul might modulate VEGF concentration to the appropriate level, which does not affect physiological vascularization, resulting in vascular normalization. 25,26 A ROCK inhibitor, fasudil, has already been shown to improve ischemia in patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In 1948 Michaelson first suggested the implication of a generic angiogenic factor in the neovascularization process occurring in retinopathy [5]; nowadays several studies stress that a key role in the development of diabetic retinopathy is indeed played by VEGF [6,7]. The expression of VEGF in diabetic retina can be regulated by different pathways, , such as Rho/Rho Kinase, ERK1/2, and Protein Kinase C (PKC) [8][9][10]. PKC is a family of at least 10 serine-threonine kinases ubiquitously expressed and able to participate in multiple cellular functions [11,12].…”
Section: Introductionmentioning
confidence: 99%